2018
DOI: 10.3390/ijms19113570
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with NaCl Promotes the Seed Germination of White Clover by Affecting Endogenous Phytohormones, Metabolic Regulation, and Dehydrin-Encoded Genes Expression under Water Stress

Abstract: This study was designed to examine the effects of NaCl pretreatment on the seed germination of white clover (Trifolium repens cv. Ladino) under water stress induced by 19% polyethylene glycol (PEG) 6000. Lower concentrations of NaCl (0.5, 1, and 2.5 mM) pretreatment significantly alleviated stress-induced decreases in germination percentage, germination vigor, germination index, and radicle length of seedlings after seven days of germination under water stress. The soaking with 1 mM of NaCl exhibited most the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
2
11
0
1
Order By: Relevance
“…Moreover, DA-6 (2 mM) also exerted distinct beneficial effects by mitigating drought-induced decreases in GV, GI, SVI, FW, RL, and SL of white clover seedlings ( Figures 1 , 2 ). These results are consistent with study of Cao et al (2018) about exogenous NaCl pretreatment during germination in white clover seeds under drought stress. The present findings indicate that seed priming with DA-6 (2 mM) could be an effective strategy to ameliorate tolerance in white clover under water deficient conditions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, DA-6 (2 mM) also exerted distinct beneficial effects by mitigating drought-induced decreases in GV, GI, SVI, FW, RL, and SL of white clover seedlings ( Figures 1 , 2 ). These results are consistent with study of Cao et al (2018) about exogenous NaCl pretreatment during germination in white clover seeds under drought stress. The present findings indicate that seed priming with DA-6 (2 mM) could be an effective strategy to ameliorate tolerance in white clover under water deficient conditions.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study has shown that exogenous polyamines application ameliorated seed germination and growth of young seedling via alteration of endogenous phytohormones in cotton (Gossypium hirsutum) under drought stress (Yang et al, 2016). Moreover, seed priming with sodium chloride enhanced germination of white clover (Trifolium repens) seeds by regulating hormonal and carbohydrate metabolism under water stress (Cao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dampak positif dari priming tersebut terhadap kadar prolin juga telah dibuktikan pada biji gandum (Tabassum et al, 2018), biji padi varietas Nagina-22 (N-22) dan Pusa-Sugandh-5 (PS-5) (Samota et al, 2017), dan biji Trifolium repens cv. Ladino (Cao et al, 2018).…”
Section: Pertumbuhan Dan Morfofisiologi Tanamanunclassified
“…Seed germination is a complex and ordered reaction process, which is regulated by endogenous phytohormones, and the phytohormone contents are controlled by key synthesis enzymes and genes [34,35]. The ratio of GA 3 and ABA in seeds is an important factor in seed germination, and their synthesis and accumulation are regulated by genes [31,36].…”
Section: Discussionmentioning
confidence: 99%